The Role of Proton Pump Inhibitors in the Management of Pediatric Eosinophilic Esophagitis - Carolina Gutiérrez-Junquera (Frontiers in Pediatrics, 2018)
Eosinophilic esophagitis (EoE) is a chronic, local, immune-mediated disorder characterized by symptoms of esophageal dysfunction and the presence of a dense eosinophilic infiltrate in the esophageal mucosa. Consensus diagnostic recommendations for EoE diagnosis included absence of histological response to a proton-pump inhibitor (PPI) trial, to exclude gastro-oesophageal reflux disease (GERD)-associated esophagitis. This recommendation exposed an entity known as “proton pump inhibitor-responsive esophageal eosinophilia” (PPI-REE), which refers to patients with EoE phenotype who are PPI-responsive and do not present GERD. In recent years, there is evidence which indicates that PPI-REE is a sub-phenotype of EoE with similar clinical, endoscopic, histological and genetic characteristics, as well as Th2-related inflammatory response. As a result, PPIs should be considered another treatment for EoE and not a diagnostic tool. PPI-REE was originally described in a case series which included two children and in two retrospective pediatric series. Later, a prospective pediatric study showed a high rate of response to PPIs at high doses with long-term maintenance at lower doses. PPI monotherapy in children with esophageal eosinophilia (EE) has been observed to reduce eotaxin-3 expression in epithelial cells and to practically reverse the allergy and inflammatory transcriptome. These data reveal that PPIs are also an effective treatment for EoE in pediatric patients, although more studies are necessary in order to define the best induction and maintenance treatment regimen, the long-term safety profile and their influence on the occurrence of fibrosis and esophageal remodeling.